Failure of high power varistor ceramic components. Issue 11 (September 2020) - Danzer, R.; Kaufmann, B.; Supancic, P.
Abstract: Ceramic varistors are electronic components which have a sharp change (over several orders of magnitude) of their electrical resistance at a well-defined voltage (switching voltage). Starting at low voltages, the resistance is large. But by exceeding the switching voltage the resistance drops dramatically and the component acts as a good conductor. Mounted parallel to a consumer, they are used as protection devices against over voltage loading. In the technical routine yearly billions of varistors are used to protect power lines, transformation stations, electronic devices, microelectronic systems or even LEDs. In service large temperature differences may come into existence, which cause severe mechanical stresses that even may destroy the components. The basic principles of the varistor behaviour are explained and examples of mechanical failure are discussed.